Implementasi Moderasi Beragama Dalam Keharmonisan Beragama Di SMA Negeri 1 Palangka Raya - Rahmat, Fauzi; Ahmadi; Anshari, M. Redha (Lembaga Dongan Dosen, 2025)
Abstract−The purpose of this study is to describe the Implementation of Religious Moderation in Religious Harmony at SMA Negeri 1 Palangka Raya. Research method The approach used in this study is a qualitative approach and a descriptive research type. The object of this study is at SMAN 1 Palangka Raya, Jl. AIS Nasution No.2, Langkai, Kec. Pahandut, Palangka Raya City, Central Kalimantan. The subjects in this study were Religious Education Teachers at SMAN 1 Palangka Raya, Central Kalimantan Province consisting of One Islamic Religious Education Teacher, One Protestant Christian Religious Education Teacher, One Catholic Religious Education Teacher, One Hindu Religious Education Teacher, and additional informants to strengthen the data from this study were the principal, vice principal and students of each religion from each religion whose religious learning was taught by the teachers mentioned earlier at SMAN 1 Palangka Raya. Data Collection Techniques used Observation, interviews, and documentation. Data validation in this study used source triangulation. The data analysis used according to Miles and Hubermen which has several steps, namely data reduction, data display (data presentation), drawing conclusions. The results of this study indicate that the implementation of religious moderation through P5 has been able to build religious harmony in SMA Negeri 1 Palangka Raya